Polygamy in the Perspective of Contemporary Islamic Law: A Normative and Contextual Analysis of Nasr Hamid Abu Zaid's Thought - Hadana, Erha Saufan; Haikal, Muhammad; Mansari, Mansari; Irwansyah, Irwansyah; Zakaria , Muzakkir; Ikhsan, Ikhsan (Syarah: Jurnal Hukum Islam dan Ekonomi, 2025)
Polygamy remains a controversial practice in Islamic society in Indonesia, especially when linked to the principles of justice and gender equality. Although Marriage Law No. 1 of 1974 and a number of other regulations have restricted polygamy through administrative and substantive requirements, practices in the field show weak control and numerous procedural violations. This gap between legal norms and social practices demonstrates the failure of the law to provide protection, especially for women. This study aims to analyze the regulation of polygamy in Indonesia from the perspective of Nasr Hamid Abu Zaid's thinking, which emphasizes the importance of maqashid al-syariah as the basis for the validity of Islamic law. This study is a normative legal study with a qualitative approach, through a documentary study of legislation, legal literature, and the thoughts of modern Islamic legal figures. The results of the study show that the regulation of polygamy in Indonesia has not fully integrated the principle of maqashid, both in the substance of the law and in its implementation in court. Legal provisions tend to be legal-formal in nature without addressing the ethical, social, and psychological dimensions of the practice of polygamy. Nasr Hamid Abu Zaid's thinking emphasizes that the permissibility of polygamy must depend on substantive justice, not merely procedural validity. This view offers a critical framework for reforming Islamic family law to be more contextual, responsive, and just. It is important to reform regulations to ensure that the law truly serves as an instrument of protection, not merely a means of legitimizing social inequality.